2021
DOI: 10.1038/s41598-021-84413-4
|View full text |Cite
|
Sign up to set email alerts
|

The histone replacement gene His4r is involved in heat stress induced chromatin rearrangement

Abstract: His4r is the only known variant of histone H4 in Drosophila. It is encoded by the His4r single-copy gene that is located outside of the histone gene cluster and expressed in a different pattern than H4, although the encoded polypeptides are identical. We generated a null mutant (His4rΔ42) which is homozygous viable and fertile without any apparent morphological defects. Heterozygous His4rΔ42 is a mild suppressor of position-effect variegation, suggesting that His4r has a role in the formation or maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Increased resistance to heat stress of H4r knock-out flies have been described recently 5 , and we found H4r enrichment on genes involved in environmental stress responses. These observations prompted us to examine how H4r localization changes upon activation of the heat stress response and after a period of recovery time following that.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Increased resistance to heat stress of H4r knock-out flies have been described recently 5 , and we found H4r enrichment on genes involved in environmental stress responses. These observations prompted us to examine how H4r localization changes upon activation of the heat stress response and after a period of recovery time following that.…”
Section: Resultssupporting
confidence: 81%
“…H4r was suggested to play a role in the chromatin formation at the loci of inducible genes such as heat shock genes 5 . We wondered whether there are changes in H4r expression upon heat shock and following recovery, which would further clarify the role of H4r in the expression of inducible genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this gene is non-essential (Figure 5C, D), we and others have found that His4r can partially compensate for loss of RD H4. 5,19,28,49 Therefore, we used CRISPR-Cas9 to engineer two His4r alleles (a deletion 5 , His4r Δ 5 and a K20A mutant, His4r K20A ) and we combined them with the appropriate RD histone mutant genotypes (Figure 5A). As shown in Figures 5C and D, homozygous loss of His4r in an H4 K20A background ( H4 K20A , His4r Δ/Δ ) reduces viability, but does not eliminate it, indicating that His4r expression is important for the observed viability of H4 K20A mutants but is not required.…”
Section: Resultsmentioning
confidence: 99%